Dancers of Incarnation: From Embodied Prayer to Embodied Inquiry - Snowber, Celeste (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2017)
In poetic, sensuous and visceral language this article explores how one liturgical dance artist, whose work as a dancer and educator was centered in dance and theology for decades was informed by an incarnational theology to break open a field of embodied inquiry now situated outside the field of theological studies. The article is in itself a dance consisting of five movements which trace the journey of a liturgical dance artist from theology to doxology, embodied prayer and embodied inquiry to dancing in nature as a cathedral. Here in creating and performing site-specific work in the natural world, all of living and being is an embodied expression of spirit. Attention is given to the Biblical foundation of bodily expression and wisdom, moving to the fields of arts-based research rooted in phenomenology and curriculum theory to open up an embodied and poetic scholarship. Here writing is artistic and scholarly, personal and universal, evoking a physicality through the senses where connections between the holy and ordinary are honoured. Dance, movement and the body are rooted in incarnational and poetic expression and represent a philosophy through the flesh where physicality and spirituality are deeply intertwined.